2002
DOI: 10.1096/fj.02-0451fje
|View full text |Cite
|
Sign up to set email alerts
|

Cord‐like Mosaic Patches in the Adrenal Cortex are Fractal: Implications for Growth and Development

Abstract: Organogenesis proceeds rapidly and faithfully during fetal development. The process includes generation of parenchyma, followed by organization into functional tissues. The method by which the growth of organ parenchyma is regulated is not known, but insight into this regulation has been obtained by studying mosaic tissues of experimental chimeras and transgenic mosaics. The patterns revealed by this procedure offer an indication of how the parenchyma was generated. In the liver, the pattern appears as islands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Quantitative comparison of radial adrenocortical stripe patterns in the experimental groups used in Validity of the 21-OH/LacZ Transgenic Mouse this study shows that they all displayed a similar corrected stripe number, suggesting that the stripe patterns in all three groups of mice are established by similar cell lineage mechanisms, irrespective of the means of generating mosaicism. This conclusion is supported by evidence from a different approach, which has established that the adrenocortical stripes displayed in rat aggregation chimeras and 21-OH/LacZ transgenic mice and rats are all fractal objects possessing identical fractal dimensions (16).…”
Section: Discussionmentioning
confidence: 82%
“…Quantitative comparison of radial adrenocortical stripe patterns in the experimental groups used in Validity of the 21-OH/LacZ Transgenic Mouse this study shows that they all displayed a similar corrected stripe number, suggesting that the stripe patterns in all three groups of mice are established by similar cell lineage mechanisms, irrespective of the means of generating mosaicism. This conclusion is supported by evidence from a different approach, which has established that the adrenocortical stripes displayed in rat aggregation chimeras and 21-OH/LacZ transgenic mice and rats are all fractal objects possessing identical fractal dimensions (16).…”
Section: Discussionmentioning
confidence: 82%
“…In our study, we found three phenotypes of adrenal cortex cords: monophenotypic EGFP-positive cords, monophenotypic EGFP-negative cords, and polyphenotypic cords, indicating that adrenal cortex cords are of polyclonal embryonic origin. Iannaccone et al (2003) reported that the adrenal cortex can regenerate after extirpation of the organ, which leaves only a remnant of the zona glomerulosa. Along with the results of our present study, this suggests that there may be a common histogenesis of the three functionally distinct zones, the zona glomerulosa, the zona fasciculata, and the zona reticularis.…”
Section: Discussionmentioning
confidence: 99%
“…Later, pulse chase experiments involving radioactive-thymidine or BrdU studies reveal a predominant labeling of subcapsular cells followed by labeling in cells that are increasingly centripetal and exclusively in the inner cortical zones (Wright et al 1973;Zajicek et al 1986). More recent molecular tracking studies support the process of centripetal and clonogenic repopulation of the adrenal cortex (Ford and Young 1963;Iannaccone et al 2003). Chimeric and transgenic mice harboring a β-galactosidase reporter, under the control of several adrenocortical-specific promoters, reveal radial expression of the transgene from the outer zG to inner zF (Weinberg et al 1985;Iannaccone et al 2003).…”
mentioning
confidence: 93%
“…More recent molecular tracking studies support the process of centripetal and clonogenic repopulation of the adrenal cortex (Ford and Young 1963;Iannaccone et al 2003). Chimeric and transgenic mice harboring a β-galactosidase reporter, under the control of several adrenocortical-specific promoters, reveal radial expression of the transgene from the outer zG to inner zF (Weinberg et al 1985;Iannaccone et al 2003). Taken together, these studies suggest that the adrenal parenchyma is composed of clonally expanded cells that extend centripetally in a cord-like fashion from the outermost layers of the cortex to the innermost cortico-medullary boundary.…”
mentioning
confidence: 95%